2008
DOI: 10.1161/circulationaha.107.727099
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandomized Comparison of Coronary Artery Bypass Surgery and Percutaneous Coronary Intervention for the Treatment of Unprotected Left Main Coronary Artery Disease in Octogenarians

Abstract: In this single-center, nonrandomized study, there were no significant differences in cardiac death or myocardial infarction and MACCE between CABG and PCI for the treatment of left main coronary artery disease in octogenarians after a mean follow-up of 2 years. Baseline EuroSCORE was the most important predictor of MACCE regardless of the type of revascularization. Randomized studies comparing both revascularization strategies in this high-risk coronary population are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 28 publications
4
79
0
1
Order By: Relevance
“…However a recent registry, which corrected for baseline differences, has shown a trend towards a better survival following surgery, despite the less invasive nature of PCI, and the lower initial morbidity. 17,18 There is a limited amount of data available from randomised trials on the influence of age on patient outcome after revascularisation. The BARI and SoS trial showed that survival was better with CABG compared with PCI irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…However a recent registry, which corrected for baseline differences, has shown a trend towards a better survival following surgery, despite the less invasive nature of PCI, and the lower initial morbidity. 17,18 There is a limited amount of data available from randomised trials on the influence of age on patient outcome after revascularisation. The BARI and SoS trial showed that survival was better with CABG compared with PCI irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…[147][148][149] Several studies comparing CABG to PCI, however, indicated that the advantage of CABG consists primarily of fewer repeat revascularizations. 139,[149][150][151][152][153][154][155] The study by Brener et al 156 indicates no significant mortality difference between PCI and CABG after 3 years of follow-up. Longer-term follow-up is needed.…”
Section: Recommendations For Pci For Unprotected Left Main Coronary Amentioning
confidence: 99%
“…• The EuroSCORE validated to predict surgical mortality was recently shown to be an independent predictor of major adverse cardiac events (MACEs) in studies with both percutaneous and surgical treatment arms [2,3]. Therefore, it can be used to determine the risk of revascularization irrespective of, and even before, the selection of treatment strategy.…”
Section: Scores and Risk Stratification Impact Of Comorbiditymentioning
confidence: 99%